Mindful Self-Compassion Training Reduces Stress and Burnout Symptoms Among Practicing Psychologists: A Randomized Controlled Trial of a Brief Web-Based Intervention - Eriksson, Terese; Germundsjö, Linnea; Åström, Elisabeth; Rönnlund, Michael (Frontiers in Psychology, 2018)
Objective: The purpose of this study was to examine the effects of a six-week web-based mindful self-compassion program on stress and burnout symptoms in a group of helping professionals. Method: In a randomized controlled trial 101 practicing psychologists were assigned to a training group (n = 51) and a wait-list control group (n = 49). The training program involved 15 min exercises per day, six days a week, for six weeks. The participants completed the Self-Compassion Scale (SCS), the Five Facets of Mindfulness Questionnaire (FFMQ), the Perceived Stress Scale (PSS), and the Shirom Melamed Burnout Questionnaire (SMBQ) pre and post intervention. Results: Eighty-one participants (n = 40 in the training group, n = 41 in the control group) took part in the pre and post assessments. Selective gains for the intervention group were observed for SCS total score (d = 0.86; d = .94 for the self-compassion scale). Levels of self-coldness were reduced following the training and mindfulness scores increased (d = 0.60). Most important, levels of perceived stress (d = .59) and burnout symptoms (d = .44 for SMBQ total, mental aspects in particular) were lower post intervention. The results largely confirmed the hypothesis that the measures of distress would be more strongly related to self-coldness than self-compassion, a pattern seen in cross-sectional analyses and longitudinal analyses, at least for burnout. Conclusions: The mindful self-compassion program appeared effective to increase self-compassion/reduce self-coldness, and to alleviate stress and symptoms of burnout in the study sample. Additional studies, preferably three-armed RCTs with long-term follow-up, are warranted to further evaluate the effectiveness of the program.